Catastrophic antiphospholipid syndrome refractory to high-dose intravenous immunoglobulin responsive to therapeutic plasma exchange. (18th August 2021) - James, Tyler E.; Martin, Leslie J.; Warkentin, Theodore E.; Crowther, Mark A.
ABSTRACT: Catastrophic antiphospholipid syndrome (CAPS) involves sudden multiorgan dysfunction from thrombosis due to antibodies that cause platelet activation and endothelial dysfunction. Treatment variably combines anticoagulation, corticosteroid use, therapeutic plasma exchange (TPE), and high-dose intravenous immunoglobulin (IVIG). A 42-year-old male with antiphospholipid syndrome (APS) presented with severe thrombocytopenia, encephalopathy, cardiac ischemia, and acral purpuric cutaneous lesions. CAPS was identified and he received heparin infusion, methylprednisolone, and IVIG. On day 7 he developed new purpuric lesions on his right foot despite detectable arterial pulses representing new microthrombosis refractory to IVIG. He was treated with TPE which resolved the right foot ischemia and eventually his CAPS. To our knowledge, this is the first patient with CAPS reported that failed initial treatment with IVIG and subsequently had excellent response to TPE. Our observations also support recent literature indicating that onset of thrombocytopenia in APS is a warning of progression to CAPS requiring treatment escalation.